Tingkat Kesejahteraan Keluarga Petani Padi di Kecamatan Sewon Kabupaten Bantul - Eska Stefani; Artita Devi Maharani; Epsilandri Septyarini (Journal of Integrated Agribusiness, 2024)
One indicator that can describe the general standard of living of society is poverty. Social inequality and poverty are problems faced by some communities. In Bantul Regency, the percentage of poor people from 2019-2021 continues to increase. There are still many rice farming households that have quite large expenses. The amount of this expenditure is due to the number of family members. With the same level of income, a farming family that has a relatively large number of family members is likely to have a lower welfare level than the welfare level of a farming family with a smaller number of family members. This research aims to analyze the level of welfare of rice farming families in Sewon District, Bantul Regency. The method in this research is quantitative descriptive. Based on the research results, it was found that 44.90% were included in the Prosperous Family III Plus, 8.16% were included in the Prosperous Family III, 8.16% were included in the Prosperous Family II, 10.20% were included in the Prosperous Family I, and 28.57% were included Pre-Prosperous Family.